Efektivitas Program Pelatihan dan Pengembangan SDM di PT Unilever Indonesia dalam Mendukung Kinerja Organisasi - Sari, Putri Delvina; S, Suwandi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the effectiveness of human resource (HR) training and development programs at PT Unilever Indonesia in supporting organizational performance. Using a quantitative method, data were collected through questionnaires, interviews, and document analysis. The results show that the training programs have improved employee competencies by 85%, enhanced employee motivation by 75%, and increased organizational productivity by 10%. The study also found that the effectiveness of training is influenced by the alignment of programs with the company’s strategic needs and employee feedback. Key recommendations include adopting digital technology in training, integrating employee feedback into program design, and providing continuous training to adapt to changing organizational needs. This study offers significant contributions to more strategic and sustainable HR management to address the evolving business dynamics.